Nobody Reads You – Once Again: Signature, Erasure, Poeture - Thiago Castañon (Global Journal of Human-Social Science, 2021)
Ulysses cunning consists in erasing his own name to become another The pretender Nobody a miniature prototype of mimesis makes Odyssey the paradigm of every literary journey Ulysses is the secret model behind recurring themes in Augusto de Campos poetry The shadow that permeates the Mallarmean motifs of the shipwreck and the elocutory disappearance of the subject singularizes the poetics of the ovonovelo author O tis is the mask that the concrete poet chooses as a paradigm of the linguaviagem to which he has been launching himself for seven decades in search of opening pores in the aporia of poetry That is why the Odyssey never ends Each reader gives a new face to the faceless mask That is why it has always been the book that Nobody reads again